Study of Multi-changeable Control Module Applicable to Physical Void Display - Yi Jung, Hyun; Seo, Bumseok; Hong, Sungdae (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study is to develop a control module for multi-changeable physical display hardware to maximize the visual effect compared to the existing physical display to stimulate the emotion of people and express more various contents.Methods/Statistical analysis: Designed a daisy chain structure and a PMW type void control unit that can be applied to a multi-changeable void display system for various image expressions, and developed a module that can simultaneously perform linear rotation motion for various types of display. Module with an arm structure was developed so that the rotation and linear motion can be performed at the same time for more variety of display forms and expression of contents.Findings: The high-speed control unit converges the advantages of the Daisy chain method and the PWM servo control method to increase the data transmission bitrate speed up to 38400 bps/sec, and it is designed to be strong against magnetic field or other RF noise using optical communication. Also, the development of the arm type mechanism enables simultaneous function of the rotation and linear motion which movement divided into 256 steps are possible to express 256 shades according to the direction of the motion and the step.Improvements/Applications: Expected that it will become a useful display system for the outdoor advertisement market by studying the form and material of the actual module surface after advanced testing in the future study.Â